Highly acidic phytase from Aspergillus niger NCIM 563 under submerged fermentation - Soni, S. K.; Khire, Jayant Malhar (FEBS Journal, 2006)

Strain improvement and up scaling of phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Shah, P.; Bhavsar, Kavita P.; Soni, S. K.; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2009)
Combination of physical and chemical mutagenesis was used to isolate hyper secretory strains of Aspergillus niger NCIM 563 for phytase production. Phytase activity of mutant N-1 and N-79 was about 17 and 47% higher than the parent strain. In shake flask the productivity of phytase in parent, mutant N-1 and N-79 was 6,181, 7,619 and 9,523 IU/L per day, respectively. Up scaling of the fermentation from shake flask to 3 and 14 L New Brunswick fermenter was studied. After optimizing various fermentation parameters like aeration, agitation and carbon source in fermentation medium the fermentation time to achieve highest phytase activity was reduced considerably from 14 days in shake flask to 8 days in 14 L fermenter. Highest phytase activity of 80 IU/ml was obtained in 1% rice bran-3.5% glucose containing medium with aeration 0.2 vvm and agitation 550 rpm at room temperature on 8th day of fermentation. Addition of either bavistin (0.1%), penicillin (0.1%), formalin (0.2%) and sodium chloride (10%) in fermented broth were effective in retaining 100% phytase activity for 8 days at room temperature while these reagents along with methanol (50%) and ethanol (50%) confer 100% stability of phytase activity at 4A degrees C till 20 days. Among various carriers used for application of phytase in feed, wheat bran and rice bran were superior to silica and calcium carbonate. Thermo stabilization studies indicate 100% protection of phytase activity in presence of 12% skim milk at 70A degrees C, which will be useful for its spray drying.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Purification and characterization of two distinct acidic phytases with broad pH stability from aspergillus niger NCIM 563 - Soni, S. K.; Magdum, A.; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2010)
Aspergillus niger NCIM 563 produced two different extracellular phytases (Phy I and Phy II) under submerged fermentation conditions at 30A degrees C in medium containing dextrin-glucose-sodium nitrate-salts. Both the enzymes were purified to homogeneity using Rotavapor concentration, Phenyl-Sepharose column chromatography and Sephacryl S-200 gel filtration. The molecular mass of Phy I and II as determined by SDS-PAGE and gel filtration were 66, 264, 150 and 148 kDa respectively, indicating that Phy I consists of four identical subunits and Phy II is a monomer. The pI values of Phy I and II were 3.55 and 3.91, respectively. Phy I was highly acidic with optimum pH of 2.5 and was stable over a broad pH range (1.5-9.0) while Phy II showed a pH optimum of 5.0 with stability in the range of pH 3.5-9.0. Phy I exhibited very broad substrate specificity while Phy II was more specific for sodium phytate. Similarly Phy II was strongly inhibited by Ag(+), Hg(2+) (1 mM) metal ions and Phy I was partially inhibited. Peptide analysis by Mass Spectrometry (MS) MALDI-TOF also indicated that both the proteins were totally different. The K (m) for Phy I and II for sodium phytate was 2.01 and 0.145 mM while V (max) was 5,018 and 1,671 mu mol min(-1) mg(-1), respectively. The N-terminal amino acid sequences of Phy I and Phy II were FSYGAAIPQQ and GVDERFPYTG, respectively. Phy II showed no homology with Phy I and any other known phytases from the literature suggesting its unique nature. This, according to us, is the first report of two distinct novel phytases from Aspergillus niger.
Keywords: Aspergillus niger; Phytase; Phytate; Poultry feed; Purification